Automatic Determination of Fiber-Length Distribution in Composite Material Using 3D CT Data. (4th May 2010) - Teßmann Teßmann, Matthias Matthias; Mohr Mohr, Stephan Stephan; Gayetskyy Gayetskyy, Svitlana Svitlana; Haßler Haßler, Ulf Ulf; Hanke Hanke, Randolf Randolf; Greiner Greiner, Günther Günther
Abstract : Determining fiber length distribution in fiber reinforced polymer components is a crucial step in quality assurance, since fiber length has a strong influence on overall strength, stiffness, and stability of the material. The approximate fiber length distribution is usually determined early in the development process, as conventional methods require a destruction of the sample component. In this paper, a novel, automatic, and nondestructive approach for the determination of fiber length distribution in fiber reinforced polymers is presented. For this purpose, high-resolution computed tomography is used as imaging method together with subsequent image analysis for evaluation. The image analysis consists of an iterative process where single fibers are detected automatically in each iteration step after having applied image enhancement algorithms. Subsequently, a model-based approach is used together with a priori information in order to guide a fiber tracing and segmentation process. Thereby, the length of the segmented fibers can be calculated and a length distribution can be deduced. The performance and the robustness of the segmentation method is demonstrated by applying it to artificially generated test data and selected real components.